Dry Pleuroscopy as a Diagnostic Tool for Lung Cancer with Minimal Pleural Effusion - Putra, Muhammad Ryan Adi; Aniwidyaningsih, Wahju; Martini, Ni Putu Laksmi Ananda (Respiratory Science, 2025)
Dry pleuroscopy is a minimally invasive procedure used to evaluate and manage pleural conditions, particularly in cases of minimal pleural effusion (mini-PE) or dry pleural dissemination (DPD). This procedure involves the induction of artificial pneumothorax to create a workspace, allowing for direct access to the pleura without relying on a significant pleural effusion, unlike wet pleuroscopy. The key advantages of dry pleuroscopy include the elimination of the need for general anesthesia, mechanical ventilation, or specialized operating rooms, thereby reducing the risk of complications and associated costs. With a sensitivity of 94.4% and a specificity of 92.8%, dry pleuroscopy is highly effective for diagnosing lung cancer and pleural metastases in cases of minimal effusion. It also aids in lung cancer staging, minimizing the need for invasive procedures like lobectomy in complex cases. Artificial pneumothorax is a key step in dry pleuroscopy. It can be achieved through blunt dissection, optical trocars, or specialized tools such as the Boutin needle or Veress cannula. Ultrasound (USG) guidance further enhances procedural accuracy and safety by reducing complications. Dry pleuroscopy provides a safe, effective, and cost-efficient diagnostic and therapeutic solution, making it preferable to methods such as video-assisted thoracoscopic surgery (VATS), especially in patients unfit for invasive procedures.